Comparison of the accuracy for three dental impression techniques and index: An in vitro study - de Avila, Erica Dorigatti; Barros, Luiz Antônio Borelli [UNESP]; Del'Acqua, Marcelo Antonialli; Castanharo, Sabrina Maria; Mollo Jr., Francisco de Assis (Japan Prosthodontic Society, 2013)
Objectives: This in vitro study compared the dimensional accuracy of stone index (I) and three impression techniques: tapered impression copings (T), squared impression copings (S) and modified squared impression copings (MS) for implant-supported prostheses. Methods: A master cast, with four parallel implant abutment analogs and a passive framework, were fabricated. Vinyl polysiloxane impression material was used for all impressions with two metal stock trays (open and closed tray). Four groups (I, T, S and MS) were tested (n = 5). A metallic framework was seated on each of the casts, one abutment screw was tightened, and the gap between the analog of implant and the framework was measured with a stereomicroscope. The groups' measurements (80 gap values) were analyzed using software (LeicaQWin - Leica Imaging Systems Ltd.) that received the images of a video camera coupled to a Leica stereomicroscope at 100× magnification. The results were statistically analyzed with Kruskal-Wallis One Way ANOVA on Ranks test followed by Dunn's Method, 0.05. Results: The mean values of abutment/framework interface gaps were: Master Cast = 32 μm (SD 2); Group I = 45 μm (SD 3); Group T = 78 μm (SD 25); Group S = 134 μm (SD 30); Group MS = 143 μm (SD 27). No significant difference was detected among Index and Master Cast (P = .05). Conclusion: Under the limitations of this study, it could be suggested that a more accurate working cast is possible using tapered impression copings techniques and stone index. © 2013 Japan Prosthodontic Society.
Keywords: Dental implant; Impression material; Impression technique; Transfer coping